(untitled) (SCIÉNDO INGENIUM, 2021)
The objective was to determine how the formulation and programming of the Annual Plan are associated with the public contracting of the Provincial Municipality of Gran Chimú 2020. Said study was developed through a quantitative, non-experimental approach, with a sample of 85 servers of the Municipality, to who were administered a questionnaire. Among the results, 55.3% consider that the formulation and programming of the annual plan is deficient. While, in Public Procurement, the prevailing level is the regular one with 65.9%, followed by the deficient level with 30.6%; Regarding the selection procedure in public contracts, 61.2% of the servers consider it to be regular. Based on the results, it is concluded that the formulation and programming stages of the Annual Contracting Plan are associated with the public contracts of the Provincial Municipality of Gran Chimú.